1997
DOI: 10.1115/1.3101860
|View full text |Cite
|
Sign up to set email alerts
|

Strain Rate Effects in Composites

Abstract: A review of the high strain rate behavior of filamentary composite materials is presented. The experimental techniques used for evaluating the dynamic performance of composites are discussed, as well as results obtained by researchers for various types of filamentary composites. Areas of research needed for expanding the information base for composites as well as the testing devices needed to obtain composite test data are chronicled. This review article contains 120 references.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(82 citation statements)
references
References 0 publications
1
80
0
1
Order By: Relevance
“…To perform the loading, it hits a shoulder put at the end of the loading bar. With this kind of device, strain rates up to 10 3 s −1 can typically be obtained [19]. A review of the use of SHPB can be found in [27].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To perform the loading, it hits a shoulder put at the end of the loading bar. With this kind of device, strain rates up to 10 3 s −1 can typically be obtained [19]. A review of the use of SHPB can be found in [27].…”
Section: Methodsmentioning
confidence: 99%
“…There have been many other high strain rate characterizations of composite materials using various adaptations of Hopkinson bar and drop weight impactors since these early experimental results [18,19]. The general trend is for increasing stiffness with increasing strain rate, particularly in the case of glass fibre composites e.g.…”
Section: Dynamic Behaviour Of Laminated Compositesmentioning
confidence: 99%
“…The matrix is also susceptible to changes in behavior under high loading rates. To further establish material characteristics under high strain rates, in 1997 Sierakowski [12] presented a review of strain rate effects in several different types of composites tested using several different test methods. He found that the fiber orientation, composite type, mode of loading, and strain rate all affect the behavior of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to investigate the strain rate sensitivity, failure modes and other behaviors under dynamic loading. Several studies have been performed on strain rate sensitivity [15]- [17]. Ochola et al [18] tested a glass fiber reinforced polymer at different strain rates.…”
Section: Introductionmentioning
confidence: 99%